Antistatic polyurethane coats with hybrid carbon nanofillers - Kowalczyk, K.; Kugler, S.; Spychaj, T. (Polimery, 2014)
Thermoplastic coats based on commercial aqueous dispersions of polyurethane and carbon nanofillers (graphite nanoplatelets and/or carbon nanotubes) were prepared and analyzed. The surface resistivity of the samples was in the range of 106—108 W (<<1 wt part/100 wt parts of dry coat of carbon nanofillers). Incorporation of carbon nanofillers into coating systems improves the hardness and thermal resistance of dry coats whereas their glass transition temperature is unaffected.